International Architecture News - Grigorieva, Anna (project baikal, 2025)
The news section presents the International Union of Architects (UIA) President Regina Gontier’s message for 2025, in which she encourages architects to strive to improve people’s well-being and quality of life through resilient architecture.
Keywords: future of humanity; architects; inclusive urban planning; sustainable architectural design